TILTED FIBER BRAGG GRATING SENSORS FOR REFRACTIVE INDEX MEASUREMENTS OF LIQUID SOLUTIONS - Harasim, Damian (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2022)
This publication presents the basic assumptions about the light guiding mechanisms in tilted fiber Bragg gratings, transmission spectra of the fiber with such structures and their sensor properties related to the occurrence of the so-called cladding modes. The light in the form of modes coupled to the optical fiber cladding causes their spectral properties to depend on the difference in the refractive indices of the surrounding medium and the fiber cladding. With the introduction of a small inclination angle of the diffraction fringes forming the Bragg grating, the cladding modes show sensitivity to changes in the refractive index of the environment of aqueous solutions, which makes the spectrum of their applications broad. This publication presents changes in the spectra of selected modes measured for solutions with a specific refractive index, shift sensitivity, and changes in the mode transmission coefficient and processing characteristics at a selected concentration range of solutions. Experimental results show that high order cladding modes respond both by shifting the central wavelength as well as by changing the transmission minimum. In selected ranges, these parameters show a linear characteristic as a function of changes in the concentration of the cane sugar aqueous solution. In the case of TFBG with a tilt angle of 8 °, the sensitivity of wavelength changes is 0.012nm / RIU for solutions with concentrations ranging from 0% to 10% by weight.